Practical considerations for delivering on the sustainability promise of fermentation-based biomanufacturing. Issue 5 (12th November 2021) - Lips, David
Abstract : Increasingly, bio-based products made via sugar-powered microbial cell factories and industrial fermentation are reaching the market and presenting themselves as sustainable alternatives to fossil and animal-based products. The sustainability potential of biotechnology, however, has been shown to come with trade-offs and cannot be taken for granted. Shared environmental impact hotspots have been identified across industrial fermentation-based products, including biomass production, energy consumption, and end-of-life fate. Based on both these patterns and our direct experience in preparing for the commercial-scale production of Brewed Protein™, we outline practical considerations for improving the sustainability performance of bio-based products made via industrial fermentation.